A microneedle patch containing measles vaccine is immunogenic in non-human primates. Issue 37 (8th September 2015) - Edens, Chris; Collins, Marcus L.; Goodson, James L.; Rota, Paul A.; Prausnitz, Mark R.
Abstract Very high vaccination coverage is required to eliminate measles, but achieving high coverage can be constrained by the logistical challenges associated with subcutaneous injection. To simplify the logistics of vaccine delivery, a patch containing micron-scale polymeric needles was formulated to encapsulate the standard dose of measles vaccine (1000 TCID50) and the immunogenicity of the microneedle patch was compared with subcutaneous injection in rhesus macaques. The microneedle patch was administered without reconstitution with diluent, dissolved in skin within 10 min, and caused only mild, transient skin erythema. Both groups of rhesus macaques generated neutralizing antibody responses to measles that were consistent with protection and the neutralizing antibody titers were equivalent. In addition, the microneedle patches maintained an acceptable level of potency after storage at elevated temperature suggesting improved thermostability compared to standard lyophilized vaccine. In conclusion, a measles microneedle patch vaccine was immunogenic in non-human primates, and this approach offers a promising delivery method that could help increase vaccination coverage.